Mechanical behavior of chontaduro (Bactris Gapisapes) fiber reinforced material composite - Villate Diaz, Juan Pablo; Vargas Ortiz, Nelson Joman (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2018)
This work presents the results of an experimental program on the mechanical behavior of chontaduro palm fibers and cement based material composites reinforced with these fibers. This palm (Bactris Gapisapes) is one of the species of great abundance in Latin America and its accelerated growth makes it an accessible material for later use. Additionally, the fibers were used as reinforcement in cement based composites using volumetric fractions of 4% extracted from the trunk of the palm. The tensile strength of the studied fibers varied of 190 MPa and the modulus of elasticity of 7,3 Gpa. The composites presented a strain softening behavior with the formation of only one crack. The tensile strength of the composite of 3 MPa. these results will serve to generate an improvement in the mechanical behavior and to be able to generate a suitable material to be used in rural constructions in load-bearing walls elements.